Branding Inklusif: Pemberdayaan UMKM Disabilitas melalui Workshop Storytelling dan Fotografi - Rofiqoh, Ifah; Komariyah, Erna Fitri; Andiyansari, Popi; Ma'rifah, Amrina Amar; Sari, Fenti Novita (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This community service program aims to boost the capacity of disabled SMEs in Malang Raya through mentoring in storytelling and product photography as a strategy to strengthen inclusive branding. The activity was implemented collaboratively by Universitas Teknologi Yogyakarta (UTY) and Lingkar Sosial Indonesia (Linksos) at the Malang Creative Center, involving disabled MSMEs from Malang City, Batu City, and Malang Regency. The process followed a participatory approach, including planning, training, and evaluation stages. The evaluation was carried out through pre-test and post-test assessments using 12 indicators of narrative and visual skills. The results showed a notable increase in the average Respondent Achievement Level from 3.63 (Good) before the training to 4.01 (Very Good) afterward. The most significant improvements appeared in photography skills and creating attractive product photos, reflecting participants’ better visual ability to present their products both aesthetically and communicatively. The progress in brand storytelling was moderate, indicating the need for additional mentoring to enhance narrative skills for building a consistent brand image. Overall, this training successfully improved the visual and narrative communication abilities of disabled SMEs participants, fostering more inclusive and competitive branding practices.